The influence of maltotriose-modified poly(propylene imine) dendrimers on the chronic lymphocytic leukemia cells in vitro: Dense shell G4 PPI - Franiak-Pietryga, Ida; Ziolkowska, Ewelina; Ziemba, Barbara; Appelhans, Dietmar; Voit, Brigitte; Szewczyk, Michal; Gora-Tybor, Joanna; Robak, Tadeusz; Klajnert, Barbara; Bryszewska, Maria (Molecular Pharmaceutics, 2013)
Chronic lymphocytic leukemia (CLL) is the most common leukemia in Europe and North America. For many years scientists and doctors have been working on introducing the most effective therapy into CLL as prognosis of survival time and the course of the disease differ among patients, which might pose a problem in treating. Nanotechnology is providing new insights into diagnosis and, compared with conventional treatments, more efficient treatments, which might improve patients' comfort by decreasing side effects. Among the various nanoparticles that are available, dendrimers are one of the most promising. The aim of this study was a preliminary assessment of the clinical value of treating CLL patients with fourth generation poly(propylene imine) (PPI) dendrimers - either unmodified (PPI-G4) or approximately 90% maltotriose-modified (PPI-G4-DS-Mal-III). PPI-G4-DS-Mal-III dendrimers have, in contrast to the cationic PPI-G4, a neutral surface charge and are characterized by low cyto-, geno-, and hematotoxicity in vitro and in vivo. For the in vitro study we used blood mononuclear cells collected from both untreated CLL patients and from healthy donors. Apoptosis was measured by an annexin-V (Ann-V)/propidium iodide (IP) assay, and mitochondrial membrane potential was estimated with use of Mito Tracker Red CMXRos. Presented results confirm the influence of dendrimers PPI-G4 and PPI-G4-DS-Mal-III on apoptosis and CLL lymphocytes viability in in vitro cultures. Both tested dendrimers demonstrated higher cytotoxicity to CLL cells than to healthy donors cells, whereas unmodified dendrimers were more hematotoxic. The surface modification clearly makes glycodendrimers much more suitable for biomedical applications than unmodified PPI-G4; therefore further biological evaluations of these nanoparticles are conducted in our laboratories. © 2013 American Chemical Society.
CRIS-Team Scopus Importer:2023-03-20
Keywords: apoptosis; chronic lymphocytic leukemia (CLL); dendrimers; modified dendrimers; poly(propylene imine) (PPI)